MagicKeys: Touch-Sensitive Tooltips for Hardware - Hinckley, Ken (2002)
Tooltips for hardware, using touch-sensitive keys. We replaced three of the F-keys (F1, F2, F3) on the MS Office Keyboard with generic task keys (Task A, Task B, Task C). The keys have touchsensitive key caps that can detect when the user is just touching the key, as opposed to depressing the key to activate it.